Absolute temperature measurement on tungsten surfaces with monochrome and bicolor IR thermography. (21st July 2021) - Guilhem, D.; Corre, Y.; Courtois, X.; Gaspar, J.; Pocheau, C.; Vives, S.
Abstract: ITER (www.iter.org ) will take advantage of tungsten (W) actively cooled plasma facing units (PFUs) in the lower divertor. These PFUs will receive a steady state plasma heat flux of 10 MW m −2 and up to 20 MW m −2 in slow transients, pushing these components to their limit. For machine protection reasons and for the study of the plasma wall interactions, temperature measurements are foreseen with mid wave infra-red (MWIR: 3–5 μ m) thermography systems to cover most of the ITER chamber, including the divertor (tungsten material) and first wall (beryllium material) [1 ]. Absolute temperature measurements from 70 °C and the cooling temperature of the PFUs, up to 3500 °C (W melting temperature at 3422 °C), are considered. Those measurements require knowledge of the emissivity of the tungsten PFU surfaces as a function of the temperature and wavelength used for the IR monochrome thermography system. This paper summarizes the emissivity measurements performed on tungsten surfaces in high heat flux test beds and the WEST tokamak [2 ] and uses the experimental emissivity values to compute the expected uncertainties in ITER (Δ T / T ) using monochrome and bicolor thermography techniques. The results show that the monochrome technique is not able to fulfill the Δ T / T < 10% requirement, while the bicolor technique is able to reduce the temperature uncertainty below 10%. Laboratory bicolor thermography measurements using a filter wheel (including six MWIR interference filters) have been successfully performed up to 830 °C with temperature uncertainty Δ T / T < 3%. In the WEST tokamak, the two dimensions emissivity map is varying by a factor of five within 27 cm along a PFU, from 0.13 to 0.65, showing that the monochrome IR thermography will have difficulties staying within the ITER requirements Δ T / T < 10% from 70 °C up to 3500 °C.